2017
DOI: 10.1016/j.rboe.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of the rotator cuff after osteosynthesis of proximal humeral fractures with locking intramedullary nail

Abstract: ObjectiveTo evaluate supraspinatus tendon integrity with ultrasound (US) in patients submitted to proximal humeral fracture (PHF) fixation with a locking intramedullary nail.MethodsThirty-one patients with PHF treated with curvilinear locking intramedullary nail, aged between 50 and 85 years, were assessed by US at six months postoperatively and clinically at six and 12 months postoperatively. The primary aim was supraspinatus tendon integrity, evaluated by US at six months postoperatively. Secondary aims incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
1
Order By: Relevance
“…It is worth mentioning that these authors also evaluated functionality using the Constant score and the Simple Shoulder Test and found that 79% of patients treated with IN had a good functional outcome. Likewise, Gracitelli et al 7 Impact of intramedullary nailing on the shoulder management of proximal humerus fractures with IN and, based on ultrasound, reported a high rate of rotator cuff injury (32% with partial tears and 13% with complete tears); however, evaluation of long-term function in these patients indicates that these tears did not have a clinically significant impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that these authors also evaluated functionality using the Constant score and the Simple Shoulder Test and found that 79% of patients treated with IN had a good functional outcome. Likewise, Gracitelli et al 7 Impact of intramedullary nailing on the shoulder management of proximal humerus fractures with IN and, based on ultrasound, reported a high rate of rotator cuff injury (32% with partial tears and 13% with complete tears); however, evaluation of long-term function in these patients indicates that these tears did not have a clinically significant impact.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies report that function after shoulder surgery is good and that patients with rotator cuff tears are usually asymptomatic, 1,5,6 but other studies report changes in shoulder function. 7,8 Hence, some authors report that plate osteosynthesis has a superior performance due to the possible effects of IN in the shoulder. [9][10][11] Considering the above, the objective of the present study was to evaluate the impact of using antegrade IN on the shoulder for the treatment of humeral shaft fractures in terms of shoulder pain, functionality, and signs of subacromial impingement.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the persistent pain and compromised shoulder function is not only correlated with the implant but to the deltasplit approach itself with damage to the critical hypovascular zone of the rotator cuff near its insertion on the humerus and/or irritation of the subacromial space [11]. Graticelli et al performed an ultrasound exam after using a curvilinear nail design and observed partial ruptures of the rotator cuff in 32% and full-thickness ruptures in 13% [12]. Gierer et al demonstrated a decrease of the functional capillar density of the supraspinatus tendon by 50% using a straight nail [13].…”
Section: Discussionmentioning
confidence: 99%
“…Graticelli et al performed an ultrasound exam after using a curvilinear nail design and observed partial ruptures of the rotator cuff in 32% and full-thickness ruptures in 13% [12]. Gierer et al demonstrated a decrease of the functional capillar density of the supraspinatus tendon by 50% using a straight nail [13].…”
Section: Discussionmentioning
confidence: 99%
“…L'absence de problèmes techniques (pas de vis dans la gouttière) et l'âge avancé des patients (78 et 85 ans) laisse penser qu'il s'agissait d'une rupture spontanée du LB, peut-être préexistante à la fracture et à l'enclouage.DiscussionNotre étude échographique, radiographique et clinique permet de confirmer notre hypothèse : l'EAP des fractures de l'humérus avec un clou huméral de 3 éme génération (clou droit, de petit diamètre, avec vis vérouillées) permet de préserver l'intégrité tendineuse de la coiffe des rotateurs dans 88% des cas et restaure la fonction de l'épaule, dans un délai relativement rapide. Au recul court de 8 mois (6 à 18 mois), nos résultats cliniques sont comparables, voire supérieures, à ceux rapportés après enclouage de 1 ère et 2 ème génération ou après fixation par plaques verrouillée(2,6,7,(19)(20)(21)(22)(23) et notre taux de consolidation est équivalent voir supérieur à celui retrouvés dans la littérature (4,20). Dans notre cohorte d'âge moyen 60 ans (20-89), la prévalence des lésions tendineuses du supraspinatus après enclouage percutané (5/40, soit 12.5%), diagnostiquée par échographie, n'est pas supérieure à celle rapportée dans les études échographiques d'une population de sujets sains et asymptomatiques (16%).…”
unclassified